Outcomes of secondary intraocular lens implantation in the Infant Aphakia Treatment Study. Issue 2 (February 2021) - VanderVeen, Deborah K.; Drews-Botsch, Carolyn D.; Nizam, Azhar; Bothun, Erick D.; Wilson, Lorri B.; Wilson, M. Edward; Lambert, Scott R.; ,
Abstract : After unilateral cataract surgery in infancy, delaying IOL implantation until age 5 years results in less myopic shift, but still some cases of high myopia at age 10½ years are reported. Abstract : Purpose: To report outcomes of secondary intraocular lens (IOL) implantation in the Infant Aphakia Treatment Study (IATS). Setting: Multicenter clinical practice. Design: Secondary analysis of patients enrolled in a randomized clinical trial. Methods: Details regarding all secondary IOL surgeries conducted in children enrolled in the IATS were compiled. Visual outcomes, refractive outcomes, and adverse events at the age of 10½ years were evaluated. Comparisons were made with eyes that remained aphakic and with eyes randomized to primary IOL placement. Results: The study included 114 infants, 57 in the aphakic group and 57 in the primary IOL group; 55 of 57 patients randomized to aphakia with contact lens correction were seen for the 10½-year study visit; 24 (44%) of 55 eyes had secondary IOL surgery. Median age at IOL surgery was 5.4 years (range 1.7 to 10.3 years). Mean absolute prediction error was 1.00 ± 0.70 diopters (D). At age 10½ years, the median logarithm of the minimum angle of resolution visual acuity (VA) was 0.9 (range 0.2 to 1.7), similar to VA in the 31 eyes still aphakic (0.8, range 0.1 to 2.9); the number of eyes with stable or improved VA scores between the 4½-year and 10½-year study visits was also similar (78% secondary IOL eyes; 84% aphakic eyes). For eyes undergoing IOL implantation after the 4½-year study visit (n = 22), the mean refraction at age 10½ years was −3.20 ± 2.70 D (range −9.90 to 1.10 D), compared with −5.50 ± 6.60 D (n = 53, range −26.50 to 3.00 D) in eyes with primary IOL ( P = .03). Conclusions: Delayed IOL implantation allows a more predictable refractive outcome at age 10½ years, although the range of refractive error is still large.